Rachel Stern: capstone - Stern, Rachel, artist and filmmaker (Colorado State University. Libraries, 2017)
The artist's statement: Our technology has made us all librarians of our memories. We have hundreds of pictures on our phones, work from years ago on our computers, and music playlists that are like time capsules. I find it funny how robots never forget, but our brains do; while humans feel emotion and robots do not. My work focuses on how robots preserve memory and emotion, despite their own lack of feeling. I play with that concept in my work with how a video or robot re-creates a memory, that will then never be forgot by the robot, but gives emotion to the viewer despite the device never understanding what it giving to the user. I focus heavily on shape, contrast and movement in my work to convey emotion. Often times, I highlight silhouettes for their shape gives detail while remaining interpretational. Another aspect of my work is a feeling of endlessness. My work has no clear ending, and no clear starting point other than the power button on the device. Our memories blur and we can get trapped in our own minds as we try to remember parts we have forgotten or where one moment started and one ended. I find more and more that the dates next to the photos on my phone fill in these gaps of knowledge, and my work demonstrates that. The feeling of artificial nostalgia mixed with emotion is where the heart of my work lies. Many science fiction movies play with the idea of robots gaining emotion, becoming self aware, able to learn, and ultimately killing humanity. While that is a reasonable fear to have, we ourselves are practically cyborgs already. Recording our memories to share online, our phones reminding us of schedules, and machines that help us create great things. As an artist my job is to remind us that our relationship with technology doesn't have to be seen as bad, but to see how it helps us remember our own humanity. Remember great moments that without our devices, we may have forgotten.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
360 Video and The Amazon have no spoken word. Shadows, Abstract Self Portrait, and Choose Your Own Adventure have no audio.
Keywords: electronic art; art; animation